Lecturer’s Gender and Their Valuation of Student Evaluation of Teaching - Engku Suhaimi, Engku Atek; Zulazhan, Ab. Halim; Hishamuddin, Salim (2015)
Student evaluation of teaching (SET) is carried out every semester at Malaysian universities and lecturers are evaluated based on student ratings. But very little is researched about what lecturers actually think about SET and whether it serves any meaningful purpose at all. This quantitative study involving six public universities on the East Coast of Peninsular Malaysia examines the extent to which male and female lecturers value their student evaluations of teaching (SET) and if their valuations differ significantly by gender. The study also elicits perceptions of male and female lecturers on the formative and summative functions the SET serves. A survey questionnaire comprising 29 Likert-scale items was employed to obtain data for this study. The respondents comprised 137 language instructors of English and Arabic proficiency courses for undergraduates from those six universities. Data were analysed descriptively and inferentially using descriptive statistics and independent sample t-test. The study produces several outcomes. The study found that although male lecturers value SET higher than their female colleagues, no significant differences are observed in their valuation of SET by gender. Also of significance is the observation that lecturers of both gender found SET more useful for formative rather than summative functions. This study itself is significant in order to understand the lecturers’ perceptions of SET which will stimulate further discussions and thinking around the issue of strengthening the teaching practice as SET itself can be an effective tool for lecturer’s development if lecturers themselves understand and value the process.